Developing Contextual Physics Worksheets through the 7E Learning Cycle on the Topics Parabolic Motion - Adi Pramuda; Sindi Patika; Soka Hadiati (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2026)
Complex abstract physics concepts, especially parabolic motion, often challenge students, necessitating development of innovative, engaging instructional materials. This study aims to evaluate the feasibility of a student worksheet designed with a contextual approach and integrated into the 7E learning cycle model. Utilizing the Research and Development (R&D) framework, this study follows the 4D model (Define, Design, Develop, and Disseminate). Data were collected through indirect communication techniques, involving structured questionnaires administered to three experts and 22 eleventh-grade students at SMAN 3 Sungai Kakap Kalimantan Barat. The results of the media validation, focusing on visual, layout, and usability, yielded an average score of 78%, placing it in the highly feasible category. Furthermore, material expert validation regarding content accuracy, linguistic clarity, and pedagogical presentation achieved a score of 89%, categorized as very appropriate. User response trials indicated that students showed high levels of interest and positive attitudes toward the worksheet, with an average score of 90% (strongly agree). These findings demonstrate that the developed worksheet is not only valid in terms of content and design but also can supporting the learning process. Consequently, this contextual-oriented worksheet is recommended as a viable teaching tool to enhance student engagement and conceptual understanding in physics education.